HLA class-I and class-II allele frequencies and two-locus haplotypes in Melanesians of Vanuatu and New Caledonia. - Maitland, K; Bunce, M; Harding, R; Barnardo, M; Clegg, J; Welsh, K; Bowden, D; Williams, T (2004)
HLA class-I and class-II allele frequencies and two-locus haplotypes were examined in 367 unrelated Melanesians living on the islands of Vanuatu and New Caledonia. Diversity at all HLA class-I and class-II loci was relatively limited. In class-I loci, three HLA-A allelic groups (HLA-A*24, HLA-A*34 and HLA-A*11), seven HLA-B alleles or allelic groups (HLA-B*1506, HLA-B*5602, HLA-B*13, HLA-B*5601, HLA-B*4001, HLA-B*4002 and HLA-B*2704) and four HLA-C alleles or allelic groups (HLA-Cw*04, HLA-Cw*01, HLA-Cw*0702 and HLA-Cw*15) constituted more than 90% of the alleles observed. In the class-II loci, four HLA-DRB1 alleles (HLA-DRB1*15, HLA-DRB1*11, HLA-DRB1*04 and HLA-DRB1*16), three HLA-DRB3-5 alleles (HLA-DRB3*02, HLA-DRB4*01 and HLA-DRB5*01/02) and five HLA-DQB1 alleles (HLA-DQB1*0301, HLA-DQB1*04, HLA-DQB1*05, HLA-DQB1*0601 and HLA-DQB1*0602) constituted over 93, 97 and 98% of the alleles observed, respectively. Homozygosity showed significant departures from expected levels for neutrality based on allele frequency (i.e. excess diversity) at the HLA-B, HLA-Cw, HLA-DQB1 and HLA-DRB3/5 loci on some islands. The locus with the strongest departure from neutrality was HLA-DQB1, homozygosity being significantly lower than expected on all islands except New Caledonia. No consistent pattern was demonstrated for any HLA locus in relation to malaria endemicity.